2016
DOI: 10.1111/gcb.13496
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐mediated effects of elevated CO2 on intra‐aggregate soil pore structure

Abstract: Soil pore structure has a strong influence on water retention, and is itself influenced by plant and microbial dynamics such as root proliferation and microbial exudation. Although increased nitrogen (N) availability and elevated atmospheric CO concentrations (eCO ) often have interacting effects on root and microbial dynamics, it is unclear whether these biotic effects can translate into altered soil pore structure and water retention. This study was based on a long-term experiment (7 yr at the time of sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 65 publications
0
15
0
1
Order By: Relevance
“…Moreover, it is likely that the mechanisms altering pore systems will vary as a function of the environmental setting. As one study showed, the aggregate properties of a sandy soil responded very differently to elevated CO 2 depending on nitrogen availability, likely due to differences in the availability of labile organic matter ( 16 ). It will also be important to determine how malleable soils with different textures and mineral compositions are when acted upon by various climatic drivers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is likely that the mechanisms altering pore systems will vary as a function of the environmental setting. As one study showed, the aggregate properties of a sandy soil responded very differently to elevated CO 2 depending on nitrogen availability, likely due to differences in the availability of labile organic matter ( 16 ). It will also be important to determine how malleable soils with different textures and mineral compositions are when acted upon by various climatic drivers.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence across diverse ecosystems for elevated CO 2 and/or O 3 effects on: (1) the quantity and quality of roots 12 , 13 , root exudates 14 and leaf litter 15 as inputs to the soil; (2) plant mineral nutrient uptake 16 , 17 , nitrogen fixation by symbiotic bacteria 18 and soil weathering, organic matter decomposition and nutrient acquisition by mycorrhizae 19 21 and (3) the extent and location of water use in the soil profile 5 . Consequently, these treatments can modify soil N mineralization, organic content, C storage, respiration 22 , 23 , N 2 O emissions 24 , and even the physical structure 25 with consequences for ecosystem-scale biogeochemistry 11 , 26 28 . Despite the recognized importance and sensitivity of the soil and plant microbiome to environmental perturbations 29 , 30 , little is known about the microbe community response and the role of soil microbes in mediating plant and ecosystem responses to eCO 2 and eO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Soil physical and chemical properties in semiarid grasslands are sensitive to land use management (Garcia‐Orenes et al, 2016; Liu et al, 2017). For soil physical structure, it is generally considered that nitrogen addition induces an increase in intra‐aggregate porosity and a simultaneous shift toward the greater accumulation of pore space in larger aggregates (Caplan et al, 2017; Chen et al, 2019; Kiani et al, 2017; Liu, Zhang, Liu, Zong, & Yu, 2018). However, nitrogen addition significantly decreased soil aggregate proportions in the present study (Figure 1d).…”
Section: Discussionmentioning
confidence: 99%
“…Several parameters, including bulk density (BD), porosity, soil moisture, aggregate stability (Caplan et al, 2017; Huang et al, 2020; Liu, Zhang, Liu, Zong, & Yu, 2018; Raiesi & Kabiri, 2016; Su et al, 2018; Sun et al, 2018), pH, total carbon and nitrogen content (Chen et al, 2017; Li, Gao, & Tang, 2016; Liu et al, 2018; Schmidt et al, 2011; Zuber, Behnke, Nafziger, & Villamil, 2017), and microbial carbon and nitrogen content (Gao et al, 2016; Leff et al, 2015; Wang, Zhang, Zhu, Yang, & Li, 2018), can be used to reflect soil properties. However, these indicators individually cannot reflect the complexity of soil structure, due to their interdependence (Raiesi & Kabiri, 2016; Zhao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%